Neck Lift to Treat Platysma Bands and Defining Cervical Angle: A Systematic Review and Pooled Analysis - Cambiaso-Daniel, Janos; Giordano, Salvatore; Agnelli, Benedetta; Bella, Ludovico La; Gualdi, Alessandro (Facial Plastic Surgery, 2024)
Many surgical techniques have been proposed to address the submental–cervical angle in neck lift. Despite the several advances, obstacles persist when dealing with platysma bands and redefinition of the obtuse cervical angle. The aim of this study was to quantify platysma bands recurrence, any neurovascular damage, and other complications following neck lift procedures involving platysma muscle. After the approval and registration on the International Prospective Register of Systematic Reviews (PROSPERO), the systematic review was performed in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A series of specific keywords and predefined MeSH terms were utilized in different search engines (Medline, PubMed, Google Scholar, and the Cochrane library databases). Primary outcome was the recurrence of platysma bands; secondary outcomes included any postoperative complications, including any nerve damage. Pooled analysis was performed using a random effects model. Twelve articles, encompassing 2,106 patients, were relevant to this issue and included data on neck lift surgery with any platysma transection outcomes. Twenty-six patients had a recurrence of platysma bands during the follow-up, with a pooled rate of 1.4%. The pooled overall nerve damage rate was 0.9%. At the reported follow-up, the pooled hematoma percentage was 1.8%, and the pooled sialoma rate was 0.3%. Even less common complications were long-lasting edema, dehiscence of the submental suspension, and skin necrosis. Cervicomental angle redefinition remains a controversial and complicated procedure, which can be approached with different maneuvers. However, more long-term outcome reports as well as standardized complication outcomes are warranted in order to compare different and new techniques.Level of Evidence III
Keywords: platysma bands; platysmotomy; neck bands; neck rejuvenation; face lift; rhytidoplasty; rhytidectomy; hematoma; ecchymosis; complications